A study of the patterns of maintenance and problems of nuclear medicine instrumentation in the Philippines - Puga, Gonzalo S. (1982)
In a study conducted by the International Atomic Energy Agency (IAEA) Medical Applications Section, it has been estimated that millions of dollars worth of nuclear medicine instrumentation acquired by developing countries have been non-functional and are, therefore, lost to productive service. This thesis aims to take a more in depth study of the actual situation in the Philippines by analyzing the patters of maintenance and instrumentation problems of three (3) typical laboratories: the Arrmed Forces of the Philippines Medical Center, the Dr. Jose R. Reyes Memorial Hospital, and the Health and Physics Modular Laboratory of the Philippine Atomic Energy Comission.
The following theoretical considerations are discussed: (1) reliability (2) effects of the environment on components; (3) Quality of the electrical power supply in developing countries; (4) Power conditioning; and (5) General maintenance principles. These topics serve as the framework by which an analysis of the Philippine situationis approached and as theoretical bases of the recommendations that are made for the pilot laboratories. Thus, a lengthy treatment of these topics is deemed necessary by this author.
The experimental investigation consists mainly of: (1) a survey of the nuiclear medicine instrumentation, seeking informations on the structure of the medical unit, on instrument operating environment and maintenance, and on instrument operation reports; and (2) a monitoring of the voltage, temperature, and rel;ative humidity conditions of the laboratories. The findings reveal significant factors which contribute to the instrument in operation and downtime, among which are: (1) not-so-ideal environment for optimum performance and long useful life of the instruments; (2) lack of protection for the instruments from the effects of AC mains fluctuations and disturbances; (3) undeveloped capability to institute/conduct repair and maintenance; (4) absence/incompleteness of appropriate service manuals; (5) unavailability of critical instrument components in the local market; and (6) some administrative constraints. Recoomendations, based on the theoretical considerations previously discussed, are then formulated. At present, some degree of implementation of the recommendations have already been achieved.
In summary, the maintenance of nuclear instruments and of any other sensitive instruments, is not a simple endeavor, more especially in the developing countries like the Philippines. Solutions to the various problems which affect instrument reliability could only be sought through collaborative efforts of all concerned. To the maintenance technicians and engineers, this is the challenge and the headache. It is , therefore, hoped that this thesis could help, even in just a small way, in providing a systematic approach towards an increased reliability of instruments.
Mimeographed.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Nuclear medicine -- Equipment and supplies. -- Philippines